The Convergence of The Systems of Education at Scottish and Ukrainian Universities in the Context of Ethic Leadership - Zagirniak, Denys; Khovrak, Inna; Perevozniuk, Viktoriia (International Journal of Engineering and Technology, 2018)
The globalization of educational space shows that university education should meet the needs of society based on the ethical principles of interaction between participants of educational process and use innovative teaching methods. Therefore the purpose of the study is to substantiate the importance of convergence of systems of education at Scottish and Ukrainian universities in order to provide ethical leadership in the field of education. A systematic approach to the realization of the purpose of the study allowed solving the main tasks: systematization of the strengths of Scottish education, justification of the impact of university social responsibility on providing ethical leadership in education, comparing the main indicators of the process of providing educational services in Scotland and Ukraine.As a result, it is established that the synergetic effect from the application of the concept of ethical leadership is achieved as a result of the interaction of all participants in the educational process, namely: the state (awareness and realization of the social mission to develop the potential of youth); universities (development of educational programs taking into account the needs of modern society and the use of teaching methods capable of forming the necessary competences for future specialists); students (interest in obtaining quality education).Â Â